2022
DOI: 10.3389/fphar.2022.936659
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein-A-I for severe COVID-19-induced hyperinflammatory states: A prospective case study

Abstract: Viral infections can promote cytokine storm and multiorgan failure in individuals with an underlying immunosuppression or specific genetic background. Hyperinflammatory states, including critical forms of COVID-19, are characterized by a remodeling of the lipid profile including a dramatic decrease of the serum levels of apolipoprotein-A-I (ApoA-I), a protein known for its capacity to reduce systemic and lung inflammation, modulate innate and adaptive immunity, and prevent endothelial dysfunction and blood coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Studies have indicated that Omega-3 polyunsaturated fatty acids (PUFA) can improve lipid metabolism by reducing triglyceride levels and increasing HDL levels, while also reducing inflammatory responses ( Ni et al, 2020 ). This approach has shown positive effects in the treatment of COVID-19 ( Sorokin et al, 2020 ; Faguer et al, 2022 ). Furthermore, the use of statins to increase HDL levels is also a current research focus in the context of COVID-19 ( Vahedian-Azimi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that Omega-3 polyunsaturated fatty acids (PUFA) can improve lipid metabolism by reducing triglyceride levels and increasing HDL levels, while also reducing inflammatory responses ( Ni et al, 2020 ). This approach has shown positive effects in the treatment of COVID-19 ( Sorokin et al, 2020 ; Faguer et al, 2022 ). Furthermore, the use of statins to increase HDL levels is also a current research focus in the context of COVID-19 ( Vahedian-Azimi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rise in LDH expression in the serum of patients with pneumonia may be due to a more intense inflammatory response in the lungs, accompanied by hypoxia, causing myocardial damage [15] . ApoA1 is an inflammatory factor with anti-inflammatory, antioxidant, and cholesterol-reversing effects, and is one of the components of HDL, which exerts its anti-inflammatory effects by inhibiting the expression of inflammatory cytokines [16] [17] . ApoA1 is closely correlated with the progression of pneumonia disease, and decreased expression may cause an increase in the expression of pro-inflammatory factors, which in turn decreases the ability of lung tissue to resist pathogens and further exacerbates the inflammatory response [18] .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of CER-001 as a salvage therapy was recently evaluated in four COVID-19 patients, three out of which showed a decline in cytokine storm and hence, recovery [ 290 ]. CER-001 administration also showed a significant reduction in HDL-SAA content, improving the native HDL–cargo characteristics [ 291 ].…”
Section: Future Outlook and Perspectivesmentioning
confidence: 99%